2014
DOI: 10.1590/0103-5150.027.003.ao15
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of postural alterations in students of Basic Education in the city of Vila Velha, Espírito Santo state, Brazil

Abstract: Introduction Human posture goes through a series of changes in the course of body growth and development, i.e., in childhood and adolescence. Moreover, during these phases, individuals are subject to risk behaviors for spinal problems, especially those related to the use of backpacks and to poor sitting posture. Objective This study aimed to detect the prevalence of postural alterations in school children enrolled in the UMEF Vila Olímpica, Vila Velha, Espírito Santo. Methods We evaluated 513 schoolchildren in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(15 reference statements)
0
3
0
1
Order By: Relevance
“…The indings of this study veri ied the presence of postural changes in the majority of the students (children and adolescents) of school age, and corroborates with the literature, such as in the study by Graup, Santos and Moro (1), which found changes in 265 adolescent students aged 15 to 18 years; Bueno and Rech (17) in 864 students from 8 to 15 years of age; Melo, Silva, Silva and Toscano (18) in 44 children and adolescents with hearing impairments aged 7 to 17 years; Vasconcelos et al (19) in 32 deaf students aged 7 to 21 years; Junior, Sampaio, Aguiar and Pinto (20) in 670 students from 11 to 19 years of age; and Rodrigues and Yamada (2) in 513 school children aged 11 to 15 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The indings of this study veri ied the presence of postural changes in the majority of the students (children and adolescents) of school age, and corroborates with the literature, such as in the study by Graup, Santos and Moro (1), which found changes in 265 adolescent students aged 15 to 18 years; Bueno and Rech (17) in 864 students from 8 to 15 years of age; Melo, Silva, Silva and Toscano (18) in 44 children and adolescents with hearing impairments aged 7 to 17 years; Vasconcelos et al (19) in 32 deaf students aged 7 to 21 years; Junior, Sampaio, Aguiar and Pinto (20) in 670 students from 11 to 19 years of age; and Rodrigues and Yamada (2) in 513 school children aged 11 to 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…Postural changes are disorders that affect children and adolescents (2) and have a 70% to 80% prevalence in the adult population, which undermine the social and professional performance, generating high inancial costs (3,4). Found in the anteroposterior planes, these changes include scoliosis, dorsal kyphosis and lumbar lordosis (1).…”
Section: Introductionmentioning
confidence: 99%
“…Schoolchildren are one of the main affected groups by scoliosis due to their environment which causes them to adopt inappropriate postures from school furniture, long permanence of sitting posture, excess weight and asymmetrical backpack support, and from their daily life habits adopted within and out of that environment [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Sendo assim, uma avaliação motora é de fundamental importância para diagnosticar e intervir, o mais precocemente possível, no atraso do desenvolvimento da criança. No entanto, os fisioterapeutas, os quais tem conhecimento técnico e científico para minimizar os diferentes problemas no desenvolvimento neuropsicomotor (DNPM) das crianças [15,16], quando inseridos na avaliação das crianças no contexto escolar, parecem estar mais direcionadas nas alterações posturais [17] do que na avaliação das habilidades motoras fundamentais durante a infância.…”
Section: Introductionunclassified